THE RELATIONSHIP AMONG PAIN, DISEASE SEVERITY, RADIOLOGICAL FEATURES AND DISABILITY IN PATIENTS WITH OSTEOARTHRITIS OF THE KNEE - Sevim Akçavuş; Aynur Karagöz; Canan Aybay; Canan Çelik; Metin Yücel (Archives of Rheumatology, 2001)
One hundred two cases having an avarage age of 67,7±8,9 (89 female, 13 male) diagnosed as knee osteoarthritis according to American Collage of Rheumatism (ACR) criteria were included into this study. Pain (knee pain scale), disease severity (Lequesne severity index), radiographic features (Kellgren-Lawrence) and disability (HAQ) were measured by objective methods and the relationship among them were investigated. Although pain severity was not related with radiographic features (p>0,05), there was a weak relationship between frequency and radiographic features (p=0,05). There was no correlation between radiographic features and disability (p>0,05). General disability was found to be related with both pain and Lequesne severity index (p<0,01).